Aplicação de princípios de ergonomia no atendimento odontológico - Yarid, Sérgio Donha [UNESP]; Diniz, Diego Garcia [UNESP]; Orenha, Eliel Soares [UNESP]; Arcieri, Renato Moreira [UNESP]; Garbin, Artênio José Isper [UNESP] (My University, 2009)
The dentist has been suggested as a professional vulnerable to labor risks mainly related to working posture. This study examined the application of ergonomics principles during the dental attendances made by university student of the last period of the Araçatuba Dental University. Twenty-four attendants were photographed and the images were digitally analyzed for the verification of 10 requirements that determine a healthy labor posture, defined by the project ISO Standard / TC 106/SC 6 N 411. It was observed that 50% of items from the check list obtained higher percentages of negative replies. The students had greater difficulties as to the correct position of the angle between the upper and lower leg when sitting, the ideal adjustment of the light focus reflector in the field of work and the patient positioning. It was concluded that the dental attendances were held without compliance with the ergonomic requirements. The greatest difficulties regarding the work posture were the sitting posture, the light beam and the patient positioning. Students need better guidance about ergonomic principles and requirements, which should occur at any time of life, but earliest they are installed, greater the benefits, assimilation and incorporation of adequate working postures will be. We need a reform that addresses all sectors of the dental system, so that learning and application of ergonomics in dentistry become effective, efficient and effective.

O cirurgião-dentista tem sido apontado como um profissional vulnerável a riscos ocupacionais principalmente relacionados à postura de trabalho. Este estudo analisou a aplicação de princípios de ergonomia durante a execução de procedimentos odontológicos efetuados por acadêmicos do último semestre da Faculdade de Odontologia de Araçatuba-SP. Vinte e quatro atendimentos foram fotografados e as imagens obtidas analisadas digitalmente para a verificação de 10 requisitos que determinam uma postura saudável de trabalho, definidos pelo projeto de Norma ISO/TC 106/SC 6 N 411. Observou-se que 50% dos itens da lista de checagem obtiveram maiores porcentagens de respostas negativas. Os alunos apresentaram maiores dificuldades quanto à posição correta do ângulo entre a parte superior e inferior da perna quando sentados, o ajuste ideal do foco de luz do refletor no campo de trabalho e o posicionamento do paciente. Concluiu-se que os atendimentos foram realizados sem a observância dos requisitos ergonômicos. As maiores dificuldades quanto à postura de trabalho tratam do ajuste do acento do mocho, do feixe de luz e do posicionamento do paciente. Os alunos necessitam de melhor orientação quanto à aplicação dos princípios e exigências ergonômicas, o que deve ocorrer em qualquer momento da vida profissional, porém quanto mais precocemente eles forem instalados, maiores serão os benefícios, assimilação e incorporação de posturas de trabalho adequadas. É necessária uma reforma que contemple todos os setores do sistema odontológico, para que a aprendizagem e aplicação da ergonomia na odontologia se tornem efetivas, eficientes e eficazes.
Application of ergonomics principles in dental care
Keywords: Ergonomics; Dental education; Worker health; Human engineer; Ergonomia; Educação em odontologia; Saúde do trabalhador; Engenharia humana